(untitled) (Journal Of Educational and Psychological Researches, 2015)
It is certain that marriage has the favor of the continuity of human kind since the Prophet Adam till now. But this important event is threatened by some justifications which lead to its delay or abandonment. In the West, sexual relations, illegal friendships, and disrespect of marriage sacredness lead to this delay. While the reasons behind the delay of marriage in the Arab world refer to high dowries, women go out to work, and the religious and scientific ignorance of the need and importance of marriage. The problem also differs according to the difference between the rural and urban regions. On one hand, we find that early marriage is a necessity in the rural regions; on the other hand, the delay of marriage is a clear and natural matter in cities. But recently a new problem starts to increase which is the marriage of the minors (under the age of 18 years) which is considered as family violence against children. Hence forth, this research deals with this problem, and analyzes it’s positive and negative sides since marriage is an institution that must be built on the right basis like equivalence, and the ability to hold the responsibility. Subsequently, age plays a great role in marriage as it may affect negatively especially if it becomes obligatory on individual. Accordingly, this research inquires the following three questions: • Is marriage of the minors preferable? • Is it a family violence or not? • What are its advantages and disadvantages? After applying the tool of the research on 125 adult female students, the research has come to the following results: - • It is not preferable for those under 18 years of age. • It is considered a family violence against children. • It has many disadvantages including an early divorce, the feeling of regret, as well as the inability to hold responsibility. But the advantage of early marriage is that it protects the young from deviation. In coordination with the Ministries of Education and Higher Education and Scientific Research, the researcher has recommended that there should be some studies that sensitize about the marriage of the minors, its social and economic influences, and its negative results in the future.